Make your home carbon-free. An open access planning tool to calculate energy-related carbon emissions in districts and dwellings - Ivan Ligardo-Herrera; Alberto Quintana-Gallardo; Christian Wolfgang Stascheit; Tomás Gómez-Navarro (Energy Reports, 2022)
Reducing the carbon emissions of buildings and whole districts is one of the main objectives of sustainable development goals. Both policymakers and end-users need reliable information to take actions that lead to achieving those goals. For this, an innovative open access planning tool has been developed to assess the effect of energy consumption on the overall carbon emissions of districts, buildings, and house units. When it comes to the end-users, it would help them know the actual environmental impact of their homes and make environmentally and financially sound decisions before investing in new equipment. The tool is meant to be an online planning service for dwelling end-users and policymakers alike; thus responding to a still unresolved demand. For this, firstly, the study focuses on the obtention of a complete catalogue of open-source conversion factors, which convert the different energy sources to carbon dioxide emissions per unit of energy. Secondly, it presents two case studies to illustrate the use of the tool. The first case study explains how an end-user could estimate the energy savings that may result from changing his domestic energy habits, equipment, and sources. The second case study uses actual data from a district in Valencia (Spain) to show how renewable sources would affect the carbon footprint of an apartment block. Both study cases show greenhouse gas emissions savings by replacing the existing equipment with more efficient ones such as heat pumps or renewable energy-based power systems like photovoltaic panels. This study concludes that providing smart tools is pivotal to planning nearly Zero-Energy Districts (nZED).